2016
DOI: 10.1145/2983531
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Norman 1986 User-Centered Model to Post-WIMP UIs

Abstract: In recent decades, “post-WIMP” interactions have revolutionized user interfaces (UIs) and led to improved user experiences. However, accounts of post-WIMP UIs typically do not provide theoretical explanations of why these UIs lead to superior performance. In this article, we use Norman’s 1986 model of interaction to describe how post-WIMP UIs enhance users’ mental representations of UI and task. In addition, we present an empirical study of three UIs; in the study, participants completed a standard three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…RBI has been used as the foundation to update earlier, yet influential, user-centered models such as the 1986 Norman Model [36]. In Poor et al [64], the authors used RBI to provide an updated view of post-WIMP interaction to evaluate whether the Norman model, more specifically the interplay between the UI and the mental representation of the UI described within, could be applied to more current interaction. They found that these post-WIMP interactions led to enhancements of mental representation of both the UI and the task.…”
Section: Contemporary Use Of Rbimentioning
confidence: 99%
“…RBI has been used as the foundation to update earlier, yet influential, user-centered models such as the 1986 Norman Model [36]. In Poor et al [64], the authors used RBI to provide an updated view of post-WIMP interaction to evaluate whether the Norman model, more specifically the interplay between the UI and the mental representation of the UI described within, could be applied to more current interaction. They found that these post-WIMP interactions led to enhancements of mental representation of both the UI and the task.…”
Section: Contemporary Use Of Rbimentioning
confidence: 99%
“…WIMP-wise small icons and texts in a list of tiles [25] are a possibility. However, using the mentioned post-WIMP paradigms in this section, we emphasized a F Pattern Layout-a form of content structuring in navigation design-by keeping an upper navigation bar as well as additional navigation elements on the left and right side of the screen.…”
Section: Content Visualizationmentioning
confidence: 99%